SPHINGOMONAS PAUCIMOBILIS INFECTIONS IN CHILDREN: NOSOCOMIAL VERSUS COMMUNITY ACQUIRED INFECTIONS - Nuri Bayram; İlker Devrim; Hurşit Apa; Gamze Gülfidan; Hande Namal Türkyılmaz; İlker Günay (Mediterranean Journal of Hematology and Infectious Diseases)
Sphingomonas paucimobilis is a causative agent of infection in immunocompromised patients, and healthcare-associated infections. Although the infections associated with S.paucimobilis occurs rarely, it has been encountered with increasing frequency in clinical settings. In the current study we noted the risk factors and clinical features of the children with S.paucimobilis infections, and the antimicrobial susceptibilities of the isolated strains among the patients. This study was conducted in Dr. Behçet Uz Children’s Hospital, Turkey, during the period of January 2005 and December 2012. The medical records of pediatric patients with positive cultures for S.paucimobilis were reviewed. Sphingomonas paucimobilis isolates were recovered from 24 pediatric patients. The median age was 4 years (ranging from 3 days infant to 15 years) and 58,3% were male. Eight (33,3%) of the patients were under 1 months of age. Among the patients; 13 (54,2%) infections were community related however 11(45.8%) infections were nosocomial infection. The median duration of hospital stay was 7 days (ranging from 4 to 22 days). The most effective antibiotics were fluoroquinolones, carbapenems, and trimethoprim/sulfamethoxazole. This is the first largest study in children to evaluate the clinical features of S. paucimobilis infections. Sphingomonas paucimobilis may cause infections in both previously healthy and immunocompromised children. Although variable antimicrobial regimens were achieved to the patients, there was no attributable fatality due to S.paucimobilis infections due to the low virulence of the bacteria.